Teaching Reading: Goals and Techniques - Adkham Suyarov (Zien Journals, 2022)
This article elucidates how to teach reading with goals and techniques. Reading is an effective activity with a purpose. A learner may read in order to get information or check excising knowledge, and in order to criticize a writer’s ideas and writing style. A reader may read the text only for relish, or to intensify knowledge of the language being read. The purpose of reading also confirms the appropriate approach to reading comprehension
Keywords: Reading; Extensive; Intensive; Scanning